The Experience of Demobilization: War Veterans in the Central European Armies and Societies after 1815 - Leighton James (War, Demobilization and Memory, 2016)
This chapter explores the varied experience of demobilization in the German armies after 1815. It points to the different experience of the various troops types, such as the volunteers, the militiamen and the regular military. It also considers how the restoration in the German states impacted on individual officers' experience of demobilization.